2009
DOI: 10.1016/j.visres.2007.12.022
|View full text |Cite
|
Sign up to set email alerts
|

The role of early visual cortex in visual short-term memory and visual attention

Abstract: We measured cortical activity with functional magnetic resonance imaging to probe the involvement of early visual cortex in visual short-term memory and visual attention. In four experimental tasks, human subjects viewed two visual stimuli separated by a variable delay period. The tasks placed differential demands on short-term memory and attention, but the stimuli were visually identical until after the delay period. Early visual cortex exhibited sustained responses throughout the delay when subjects performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 105 publications
(127 reference statements)
8
64
1
Order By: Relevance
“…2 shows a representative example of the developing activation time series across visual areas after the onset of the sample stimulus in the late-cueing experiment. In line with earlier studies of delayed discrimination of orientation (Harrison and Tong, 2009;Offen et al, 2009;Serences et al, 2009), the observed drop to baseline between sample and test stimuli was confirmed in all visual areas by a GLM. As expected, all visual stimuli (sample stimulus/memory test stimulus/discrimination test stimulus) produced highly significant main effects in all ROIs (t(5) > 5.1, p b 0.004).…”
Section: Behavioral Datasupporting
confidence: 90%
See 1 more Smart Citation
“…2 shows a representative example of the developing activation time series across visual areas after the onset of the sample stimulus in the late-cueing experiment. In line with earlier studies of delayed discrimination of orientation (Harrison and Tong, 2009;Offen et al, 2009;Serences et al, 2009), the observed drop to baseline between sample and test stimuli was confirmed in all visual areas by a GLM. As expected, all visual stimuli (sample stimulus/memory test stimulus/discrimination test stimulus) produced highly significant main effects in all ROIs (t(5) > 5.1, p b 0.004).…”
Section: Behavioral Datasupporting
confidence: 90%
“…We developed an experimental design that, within the general linear model (GLM) framework, allows the dissociation of encoding processes from the retention and retrieval phases. A common finding when adopting such a univariate fMRI analysis approach to VSTM tasks is large and consistent responses to the stimulus components, but a drop to baseline activity levels during the maintenance phase (e.g., Offen et al, 2009). However, we reasoned that if VSTM encoding stretches into the early retention interval, and thus leads to prolonged recruitment of neural populations involved in memory encoding, we should observe larger and more extensive BOLD-responses from those populations during the encoding phase compared to other tasks requiring similar sensory processing, but no initiation of a memory trace.…”
Section: Introductionmentioning
confidence: 99%
“…Offen et al (2009) found robust activation of V2, V3 and LO (a portion of the lateral occipital complex) in human observers in a delayed discrimination task. Some activation was seen in V1, V3A/B and hV4.…”
Section: Further Evaluation Of Locusmentioning
confidence: 88%
“…These results make it difficult to disentangle effects due to imagery versus attention (but, see Offen, Schluppeck & Heeger [2009] for evidence that attention and visual short-term memory rely on different processes in early visual cortex). In addition, Grossberg (2000) has suggested that a combination of mismatched attentional and topdown expectancy effects can give rise to the experience of perceiving a stimulus in its absence in the case of schizophrenic hallucinations.…”
mentioning
confidence: 99%